The Effect of Economic Growth, Poverty and Wages On Tax Revenue - Fibria Anggraini Puji Lestari; Yolanda Yolanda (Eduvest - Journal of Universal Studies, 2022)
Taxes are a source of state revenue, economic growth conditions can have an impact on the taxation sector, besides that poverty and wage factors can also affect state tax revenues. The purpose of this study was to determine the magnitude of the effect of economic growth, poverty and wages on tax revenues. The sample used in this study was 30 provinces in Indonesia. The research method used in this research is descriptive quantitative analysis method. Using secondary data during 1991-2021 and analyzed with time series data regression. The results of the research conducted can be seen that economic growth has a positive and significant effect on tax revenue, poverty has a negative and significant effect on tax revenue, positive and significant effect on tax revenue. as well as tax revenue